1970
DOI: 10.1002/ijch.197000055
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Analysis of Clays in Soils Developed from Basalts in Australia

Abstract: Clay mineralogical analyses were made of red soils and black soils developed from southern Victoria, Australia. The clays of the black soils are dominantly montmorillonite (39%) and vermiculite (16%) but have an average siliceous allophane content of 17%. The clays of the red soils are dominantly kaolinite and halloysite (26%) and chlorite (30%) but have an average halloysitic allophane content of 21%. Two to eight per cent of mica and quartz occur in both. A longer period of eolian dust accumulation and concu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The observation that, e.g. in Australia, black shallow smectitic soils on basalt occur on upper slopes replaced by deep red kaolinitic soils (krasnozems) on lower slopes (Briner and Jackson, 1970) does not contradict this general idea but supports it. The shallow erosional soils represent the initial phase of soil formation which is, as shown above, represented by smectites.…”
Section: Discussionmentioning
confidence: 90%
“…The observation that, e.g. in Australia, black shallow smectitic soils on basalt occur on upper slopes replaced by deep red kaolinitic soils (krasnozems) on lower slopes (Briner and Jackson, 1970) does not contradict this general idea but supports it. The shallow erosional soils represent the initial phase of soil formation which is, as shown above, represented by smectites.…”
Section: Discussionmentioning
confidence: 90%
“…1). Briner and Jackson (1970) proposed a SiOJR20 3 molar ratio method of calculation to eliminate the interference by other iron-rich phyllosilicates such as partially chloritized montmorillonites which may be dehydroxylated along with kaolinite. El-Attar and Jackson (1973) reported that large quantities of silica and alumina were dissolved from 2:1 layer silicates by the 0.5 N NaOH extraction after dehydroxylation of the clay fractions of montmorillonitic soils in Nile River sediments.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the values of SIO2/A1203 molar ratios, Jackson (1969) differentiated between very siliceous amorphous material with ratios from 2.9 to over 4, siliceous amorphous material with molar ratios of 2.8 to 1.4 and aluminous amorphous material with ratios of 1'1 _4-0.3. These criteria as well as other data available in the literature (Briner and Jackson, 1970;Mokma et ai., 1973), are not strictly applicable in this study since the SiOz/AI203 molar ratio of sample 3-2 (Table 2) was calculated from the elemental analysis rather than from the Na or KOH extract.…”
Section: Methodsmentioning
confidence: 92%